Topographic organization across foveal visual areas in macaques - Li, Hangqi; Hu, Danling; Tanigawa, Hisashi; Takahata, Toru (Frontiers in Neuroanatomy, 2024)
Introduction While the fovea on the retina covers only a small region of the visual field, a significant portion of the visual cortex is dedicated to processing information from the fovea being a critical center for object recognition, motion control, and visually guided attention. Despite its importance, prior functional imaging studies in awake monkeys often focused on the parafoveal visual field, potentially leading to inaccuracies in understanding the brain structure underlying function. Methods In this study, our aim is to unveil the neuronal connectivity and topography in the foveal visual cortex in comparison to the parafoveal visual cortex. Using four different types of retrograde tracers, we selectively injected them into the striate cortex (V1) or V4, encompassing the regions between the fovea and parafovea. Results V1 and V4 exhibited intense mutual connectivity in the foveal visual field, in contrast to the parafoveal visual field, possibly due to the absence of V3 in the foveal visual field. While previous live brain imaging studies failed to reveal retinotopy in the foveal visual fields, our results indicate that the foveal visual fields have continuous topographic connectivity across V1 through V4, as well as the parafoveal visual fields. Although a simple extension of the retinotopic isoeccentricity maps from V1 to V4 has been suggested from previous fMRI studies, our study demonstrated that V3 and V4 possess gradually smaller topographic maps compared to V1 and V2. Feedback projections to foveal V1 primarily originate from the infragranular layers of foveal V2 and V4, while feedforward projections to foveal V4 arise from both supragranular and infragranular layers of foveal V1 and V2, consistent with previous findings in the parafoveal visual fields. Discussion This study provides valuable insights into the connectivity of the foveal visual cortex, which was ambiguous in previous imaging studies.